2012
DOI: 10.1007/s10658-012-0076-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of Botryosphaeriaceae species in New Zealand grapevine nurseries

Abstract: To determine presence of infection by botryosphaeriaceous fungi in plant materials from different grapevine nurseries, different types of grafted plants and cuttings were requested from nine grapevine nurseries around New Zealand. Of the 311 propagation materials and plants collected, 23 % were infected by botryosphaeriaceous fungi. The highest incidence was in failed grafted plants (33 %), followed by Grade 1 plants (28 %), rootstock cuttings (19 %), scion cuttings (17 %) and Grade 2 plants (7 %). For grafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…() and Baskarathevan et al . (), and sequence analyses of the ITS region of rDNA (Billones‐Baaijens et al ., ). The aligned DNA sequences of the representative isolates for each species from the nurseries and the neighbour‐joining tree were submitted to TreeBASE.org (accession number TB2:S13227) (Billones‐Baaijens et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…() and Baskarathevan et al . (), and sequence analyses of the ITS region of rDNA (Billones‐Baaijens et al ., ). The aligned DNA sequences of the representative isolates for each species from the nurseries and the neighbour‐joining tree were submitted to TreeBASE.org (accession number TB2:S13227) (Billones‐Baaijens et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Amponsah et al (2011) also reported that New Zealand vineyard isolates of N. luteum, N. australe, N. parvum and D. mutila were pathogenic, being able to cause necrotic lesions on excised and attached green shoots and trunks of five grapevine varieties. Billones-Baaijens et al (2013) demonstrated that the same Botryosphaeriaceae species that were prevalent in New Zealand vineyards were present in failed and symptomless young grafted plants and propagation cuttings. They found these pathogens in 5-63% of samples submitted and in materials from eight out of nine nurseries.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…luteum, N. australe, Diplodia mutila, Botryosphaeria dothidea and D. seriata, with N. parvum being the predominant species. The same six species were also the most commonly isolated from plants and propagation materials from nine nurseries (Billones-Baaijens et al 2013). In vineyards, conidia produced on diseased tissue have been reported to be the main inoculum sources, being splash dispersed to infect grapevine tissue through wounds (van Niekerk et al 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Neofusicoccum luteum was first reported in New Zealand in 1985 on kiwifruit (Pennycook & Samuels, ) and the first report of N. australe in New Zealand was on grapevines (Amponsah et al ., ). Although both species are found in grapevine nurseries and vineyards, their relative prevalence differed in grapevine nurseries (57% N. luteum and 7% N. australe ; Billones‐Baaijens et al ., ) and vineyards (14% N. luteum and 11% N. australe ; Baskarathevan et al ., ). New Zealand surveys and pathogenicity studies have indicated that these two species are important pathogens of grapevines and significantly contribute to dieback and decline disease (Amponsah et al ., ; Baskarathevan et al ., ; Billones‐Baaijens et al ., ).…”
Section: Introductionmentioning
confidence: 99%